Gaya kepemimpinan yang efektif pada Generasi X dan Generasi Millenials - Sentika, Sarah; Prianka, Winda Gafrilia; Asqalani Rifai, Muhammad Syakib; Rusinzika, Sandra (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
It is difficult to manage human resources across generations within an organization. This study aims to analyze leadership styles that are suitable for generation X and millennials, where the independent variables consist of transformational leadership (X1), ethical leadership (X2), and servant leadership (X3), while motivation is the dependent variable (Y). This research is descriptive because it examines and analyzes a problem or phenomenon. This study's sample consists of MSME actors from Bandung and Sumedang from the X and Millennial generations. The results of this study indicate that the most appropriate leadership style in generation X, based on the order of the average score, is ethical leadership (86.49%), transformational leadership (84.94%), and servant leadership (85.77%), while the most suitable leadership styles for the millennial generation, based on the order of the average score, are ethical leadership (93.82%), transformational leadership (90.05%), and servant leadership (85.56%). Even though the order of leadership styles between generation X and millennials is the same, there are differences in the highest average score in the Ethical Leadership variable indicator.